Misuse of Prescription Opioid Medication among Women: A Scoping Review - Natalie Hemsing; Lorraine Greaves; Nancy Poole; Rose Schmidt (Pain Research and Management)
Background. National data from Canada and the United States identify women to be at greater risk than men for the misuse of prescription opioid medications. Various sex- and gender-based factors and patient and physician practices may affect women’s use and misuse of prescription opioid drugs. Objectives. To explore the particular risks, issues, and treatment considerations for prescription opioid misuse among women who experience chronic noncancer pain and trauma. Methods. A scoping review for articles published between January 1990 and May 2014 was conducted on sex- and gender-based risks and treatment considerations among women who experience chronic noncancer pain and trauma. Results. A total of 57 articles were identified. The present narrative review summarizes the specific risks for the misuse of prescription opioid medication among women who have experienced violence and trauma, Aboriginal women, adolescents and young women, older women, pregnant women, women of a sexual minority, and transwomen. Discussion. The majority of the literature is descriptive, with few studies that evaluate approaches and interventions to respond to the issue of chronic pain, trauma, and misuse of prescription opioids among women, particularly vulnerable subgroups of women. Conclusions. Trauma-informed and women-centred approaches that address women’s vulnerabilities and complex needs require further attention.